Development of Discovery Learning-Based Student Worksheets on Chemical Equilibrium Material - Februanti, Nita; Sahputra, Rachmat; Sartika, Rody Putra (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to produce discovery learning-based worksheets on chemical equilibrium material through expert judgment. The method in this study is Research & Development (R&D) with a Four-D development model which is limited to the Develop stage, based on a feasibility test. The subject of this research is student worksheets (LKPD) based on discovery learning on chemical equilibrium material for class XI students of SMA Negeri 1 Kuala Mandor B. Data collection techniques used are measurement techniques and direct communication techniques. The data collection tool is in the form of a LKPD feasibility assessment sheet. The feasibility test was carried out based on the material aspect, namely 92% with a very feasible category, the language aspect was 95.2% with a very feasible category and the design aspect was 95% with a very feasible category. Thus, it can be concluded that the worksheets based on discovery learning on chemical equilibrium materials developed are feasible. for use in learning.